ANALISIS RASIO KEUANGAN UNTUK MENILAI KINERJA KEUANGAN PT DARYA VARIA LABORATORIA TBK TAHUN 2019 – 2023 - Tyara Pratiwi Poernomoputri; Zeze Zakaria Hamzah; Noni Rahmat Yani Giawa (Institut Teknologi dan Bisnis Dewantara, 2025)
Assessing a company's financial performance is crucial for evaluating its financial condition, its ability to face economic challenges, and for measuring overall corporate achievement. This study aims to assess the financial performance of PT Darya Varia Laboratoria Tbk during the period from 2019 to 2023. The financial ratios analysed in this study include liquidity, solvency, profitability, and activity ratios, with the goal of providing a comprehensive overview of the company’s ability to manage its assets, liabilities, and overall profitability. The research method used is financial ratio analysis with a quantitative approach to evaluate changes in the company’s financial performance over the five-year period, based on available financial statement data. The results show that the financial performance of PT Darya Varia Laboratoria Tbk fluctuated from year to year, as reflected in the variations of its financial ratios. These fluctuations were caused by increases or decreases in various financial statement components, such as sales, cost of goods sold, operating profit, current assets, total assets, and others.